1987
DOI: 10.1210/jcem-64-4-744
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Differentiated Trophoblast Function by Epidermal Growth Factor: Relation of Immunohistochemically Detected Cellular Epidermal Growth Factor Receptor Levels*

Abstract: The effects of epidermal growth factor (EGF) on the production and secretion of hCG and human placental lactogen (hPL) by cultured placental tissues were investigated in relation to immunohistochemical measurements of cellular EGF receptor levels in the placenta. Explants of trophoblastic tissues obtained from normal early and term placentas were cultured in the presence or absence of EGF (100 ng/mL) with or without processing inhibitors (bacitracin, 1 mg/mL; colchicine, 100 microM; chloroquine, 100 microM) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
45
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(49 citation statements)
references
References 31 publications
4
45
0
Order By: Relevance
“…ErbB-1 in very early placentas was immunolocalized in C-cells, whereas ErbB-1 in early, mid and term placentas was immunolocalized in S-cells. These results are consistent with our previous reports using immunohistochemical analysis (6,31). These findings imply that BTC in S-cells may act in a paracrine fashion in very early placentas and in an autocrine fashion in early and mid placentas via ErbB-1 in villous trophoblasts.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…ErbB-1 in very early placentas was immunolocalized in C-cells, whereas ErbB-1 in early, mid and term placentas was immunolocalized in S-cells. These results are consistent with our previous reports using immunohistochemical analysis (6,31). These findings imply that BTC in S-cells may act in a paracrine fashion in very early placentas and in an autocrine fashion in early and mid placentas via ErbB-1 in villous trophoblasts.…”
Section: Discussionsupporting
confidence: 93%
“…In our previous study regarding the biological effect of EGF in human placenta, we found that EGF in C-cells stimulates trophoblast proliferation in very early placentas, whereas EGF in S-cells stimulates and regulates differentiated trophoblast function in early placentas (8,32). It is evident that EGF induces the differentiation in explants of trophoblastic tissues obtained from normal early placentas (31) and in long term serumfree culture of isolated trophoblasts (33). Little information is, however, available regarding the role of BTC on villous trophoblasts in early placentas.…”
Section: Discussionmentioning
confidence: 99%
“…As a function of culture time, a parallel study was performed to determine the level of secreted intact hCG and its free a and J3 subunits, using specific monoclonal antibodies and radiometric assay (Bellet et al, 1986;Ozturk et al, 1987). In contrast to data obtained from either term placenta cultured cells (Kliman et al, 1986), or from first trimester explant cultures (Maruo et al, 1987) (Jameson et al, 1987;Zhou et al, 1987;Nulsen et al, 1988). Moreover, the addition of cAMP stimulated the secretion of hPL by cultured cells, in contrast to previous results obtained for term placenta (Zeitler et al, 1983).…”
Section: Discussionmentioning
confidence: 82%
“…It is known that EGF plays a vital role in differentiation of human cytotrophoblasts (Maruo et al, 1987;Morrish et al, 1997). These cells act as the progenitor cells of syncytiotrophoblasts, which form the outer layer of placental villi representing the structure of placenta that is free floating in maternal blood.…”
mentioning
confidence: 99%